AEROBIC BACTERIAL CONTAMINATION IN PLATELET CONCENTRATES AT THE REGIONAL BLOOD CENTRE, PESHAWAR - Muhammad Ibrahim,; Muhammad Nisar Khan,; Muhammad Arif,; Syed Abbas Anwar,; Noor e Saba,; Yousafzai, Yasar Mehmood (Journal of Ayub Medical College Abbottabad, 2023)
Background: Platelet concentrates play a crucial role in transfusion medicine, aiding in the management of various medical conditions, including haemorrhage, thrombocytopenia, and platelet dysfunction. However, their storage conditions at 22° C present an optimal environment for bacterial growth, making them susceptible to contamination. Of particular concern is the transmission of microorganisms from the skin flora during the phlebotomy process, which can lead to the transfusion of contaminated platelet concentrates. Such contamination poses significant risks to patients, potentially resulting in morbidity and mortality. Determining the frequency and identifying causative organisms of bacterial contamination in platelet concentrates. Methods: It was a descriptive cross-sectional study conducted at the Institute of Pathology and Diagnostic Medicine, Khyber Medical University, and the Regional Blood Center in Peshawar from May to October 2021, spanning a duration of six months. The study included 500 participants aged between 18 and 50 years (mean: 28.13±7.67 years. A simple convenient sampling technique was employed. Blood products underwent screening for Hepatitis B, Hepatitis C, HIV, Syphilis, and Malaria. Leaked units were excluded from the study. Platelets were prepared using a Cryofuge and subsequently subjected to culture media. Results: The mean age of the participants included in the study was 28.13±7.67 years, with an age range of 18 to 50 years. Out of the total sample size of 500, there were 483 (96.6%) male participants and 17 (3.4%) female participants. Among the collected samples, bacterial growth was observed in only 11 (2.2%) platelet concentrates. The isolated organisms were Staphylococcus epidermidis, found in 7 (1.4%) platelet concentrates, and Staphylococcus aureus, found in 4 (0.8%) platelet concentrates. Conclusion: Bacterial contamination of platelet bags is higher compared to developed countries. Therefore, implementing quality control procedures is necessary to reduce the risk of bacterial contamination in platelet concentrates. Additionally, employing enhanced skin disinfection techniques at the phlebotomy site can significantly minimize bacterial contamination.